Learning Interests with Talking Drawing Strategy of Inclusive Primary School Students in Surakarta - Sari, Erma Kumala (Proceeding of International Conference on Teacher Training and Education, 2016)
A learning method is necessary in supporting learning activity. Thus, a learning method applied in inclusive school should reinforce learning interests and outcomes of students, both normal students and students with special needs. This research aims to determine the effect of Talking Drawing Strategy (TDS) to improve learning interests of the inclusive primary school students in Surakarta. The research applied random sampling technique with 52 respondents of fourth-class students in two inclusive primary schools in Surakarta. The respondents consist of normal students and students with special needs. Data were gathered by observations of studentsâ learning interests and a questionnaire about the students learning interest with TDS. Based on descriptive statistical analysis, the research showed that learning activities with TDS can decrease the negative learning behaviours up to 50% in all respondents, 52% in normal respondents, and 45% in respondents with special needs. The research also revealed that (1) 79% of the students like to learn with TDS; (2) 79% of the students stated that TDS is useful in understanding subject matter; and (3) 52% of the students stated that learning with TDS is easy to do. To sum up, TDS improves the learning interests of the inclusive primary school students in Surakarta.